POTENSI AGRIBISNIS USAHATERNAK AYAM BROILER DI KOTA KENDARI - Sani, La Ode Arsad (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2014)
This research was conducted in Kendari City at Southeast Sulawesi Province on July to August 2012. The aims of this research are to analyze the channels and marketing institution, to know part of price is accepted by broiler farmer and marketing institution, to analyze the rate of marketing margin of broiler farmer, the rate of marketing institution and consumer with the rate of broiler farmer income. This research is expected can be used as: (1) as the information and consideration for broiler farmer (2) as  the consideration  for broiler farmer in  the marketing,  as  a consideration  to  determine the policy,  to  improve productivity and  patterning of marketing in Kendari City. The research material is a good broiler farmer miter or not miters to the company with production capacity between 2.500 to 4.000 tails. The method of the research is survey research. While to determine the location of this research by using purposive sampling and took 35 respondents consisted 5 broiler farmers and 30 intermediary traders by using purposive. Tabulation data was obtained and analyzed by marketing margin and the rate of broiler farmer income were elaborated  on  descriptive  manner.  The  result  showed  that  the  broiler  marketing channel at Kendari City involved 4 types with two marketing institutions involved: trader collector and trader retailer, the part of price received by broiler farmer from the last consumer was 68,8% whereas the part of price received by marketing institutions was 31,2%, marketing margin on the broiler price from broiler farmer to the last consumer was Rp.14.150 tails-1  (the sale of broiler in the level of broiler farmer was Rp.31.200 tails-1, broiler farmer to the trader collector was Rp. 9.000 tails- 1  and trader collector to retailers was 5.150 tails-1) and the rate of the broiler farmer income in Kendari City was Rp.17.046.139 cycle-1 or Rp.5.013 tails-1 cycle-1.   Key words: marketing, income, broiler, marketing margin